HUBUNGAN ANTARA STATUS GLASSGOW COMA SCALE DENGAN ANGKA LEUKOSIT PADA PASIEN TRAUMA KEPALA YANG DIRAWAT INAP DI RSUD Dr MOEWARDI SURAKARTA - SOFIYAN, ADE (2009)
Background. The head traumatic incidence in the Intensive Care Unit is high enough and head traumatic is one of main death causes of traffic crashes and it can also cause infection. In the context of assessing head traumatic infection and GCS, therefore, need treatment for one of the indicators by seeing the leucocytes level. Objective. To know the relation of Glasgow coma scale status and leucocytes level of the in-patients in RSUD Dr. Moewardi Surakarta. Research Method. It is an analytical descriptive research using cross sectional approach. The data are collected from the medical records in RSUD Dr. Moewardi Surakarta from October to November 2009. The sampling used is total sampling. The number of sample is 40 patients with head traumatic in RSUD Dr. Moewardi Surakarta on 2008 consisting of light head traumatic is 19 cases, middle head traumatic is 5 cases, and severe head traumatic is 16 cases. Result. The data are tested statistically using Kruskal Wallis of SPSS 16. The result of the study shows that there is meaningful relation of Glasgow coma scale status and leucocytes level of the in-patients in RSUD Dr. Moewardi Surakarta. Conclusion. There is relation of Glasgow coma scale status and leucocytes level of the in-patients with head traumatic in RSUD Dr. Moewardi Surakarta.